BERKEBUN DAN BUDIDAYA IKAN DI KAWASAN PERKOTAAN: APLIKASI BUDIKDAMBER SEBAGAI SOLUSI PENINGKATAN KEMANDIRIAN PANGAN UPAYA MENDUKUNG GREEN ECONOMY - Karina, Indira; Ikhlas, Boni; Desmiati, Ira; Aisyah, Siti; Munzir, Abdullah (Smart Education, 2024)
Abstract: The Lubuk Tempurung Indah Fish Farming Group mainly cultivates tilapia. Since the last 5 years, agricultural land and fish farms in Kuranji Village have been disappearing and replaced by housing complexes. This has caused production from farmers and fish farmers to decline. To overcome this problem, the solution designed is skills training on the technical aspects of BUDIKDAMBER or fish farming in a bucket with a hydroponic system at the top. Assistance in BUDIKDAMBER and hydroponic business management starting from planning, organizing, directing to supervising the products produced and assistance in product marketing through improving marketing strategies by utilizing internet networks or websites (e-commerce). The result of this activity is the emergence of new products resulting from the diversification of the application of Budikdamber science and technology, namely live stalls (vegetables and fruits) and growing TOGA (family medicinal plants) and catfish from Budikdamber. The formation of business management ranging from planning, organizing, directing to supervising the products produced. Partners are able to make well-organized financial and administrative bookkeeping, and are able to market products utilizing the internet network or website (e-commerce).Keywords: BUDIKDAMBER, Hydroponics, Marketing, Business Development. Abstrak: Kelompok Budidaya Ikan Lubuk Tempurung Indah sebagian besar hanya membudidayakan ikan nila. Sejak 5 tahun terakhir lahan pertanian dan budidaya ikan di Kelurahan Kuranji semakin menghilang dan berganti dengan komplek perumahan. Ini menyebabkan produksi dari petani dan pembudidaya ikan semakin menurun. Untuk mengatasi masalah tersebut solusi yang dirancang adalah pelatihan keterampilan pada aspek teknis BUDIKDAMBER atau budidaya ikan dalam ember dengan sistem hidroponik di bagian atasnya. Pendampingan dalam manajemen usaha BUDIKDAMBER dan hydroponic mulai dari perencanaan, pengorganisasian, pengarahan hingga pengawasan terhadap produk yang dihasilkan dan pendampingan pada pemasaran produk melalui peningkatan stategi pemasaran dengan memanfaatkan jaringan internet atau website (e-commerce). Hasil dari kegiatan ini adalah munculnya produk baru hasil diversifikasi penerapan IPTEK Budikdamber yaitu warung hidup (sayur dan buah-buahan) dan menanam TOGA (tanaman obat keluarga) serta lele hasil Budikdamber. Terbentuknya manajemen usaha mulai dari perencanaan, pengorganisasian, pengarahan hingga pengawasan terhadap produk yang dihasilkan. Mitra mampu membuat pembukuan keuangan dan administrasi yang tertata baik, dan mampu memasarkan produk memanfaatkan jaringan internet atau website (e-commerce).Kata kunci: Budikdamber, Hidroponik, Pemasaran, Pengembangan Usaha.